'Pumping Iron` - Assessing post exercise muscle swelling using a hand-held 3D scanner - Schroeder, J.; Schmidt, M.; Spychala, A. (Journal of Australian Strength and Conditioning, 2020)
Upper arm limb volumes were assessed in order to quantify the "pump" feeling representing a temporary acute exerciseinduced muscle swelling using a hand-held 3D scanner. In a case series study, the right upper arm volume of 14 experienced male athletes (31.0 ± 7.8 years, BMI 23.9 ± 3.0 kg/m²) was assessed before and after a fatiguing exercise protocol organised as compound super-sets (30 min in total, 3 coupled arm flexion and extension exercises, each 2 sets with 30 s rest and a load allowing 10-12 reps) using a three-dimensional hand-held 3D scanner (Artec Studio 9.0: Artec Group, Santa Clara, CA, USA). The procedure`s reproducibility was determined as test-retest reliability (ICC [95%CI], SEM, CV%). External validity was confirmed using water displacement as a `gold` standard (R², Bland-Altman bias [95%CI]). 3D scanning was reliable (ICC3,1 = 0.97 [CI 0.92-0.99], SEM = 3.4%, CV = 2.5%) and valid (R² = 0.98) with a method`s bias of 3%. Exercise-induced limb volume increases were quantified as 14.0 % (±4 %) ranging from 7 % to 22 % (P <.001, dz = 4.0). Thus, the subjective feeling of being pumped up was objectified as meaningful limb volume increases, which has not been previously reported in scientific literature. The use of the 3D scanner used in this study was a valid and reliable tool for measuring upper limb volume. Applicability was demonstrated, suggesting the usefulness for elite athletes` coaching or scientific monitoring purposes of long-term muscle hypertrophy training sequences or detraining effects, e.g. after injury. Due to its portable character, 3D scans may be applied directly in the athletes` training environment. Moreover, 3D scans might be applied in order to monitor lymphoedema in the field of exercise therapy.